Systematic screening for primary immunodeficiencies in patients hospitalized for severe infection in pediatric intensive care unit - Anna Deguet; Marie-Gabrielle Vigue; Claire Lozano; Julien Baleine; Christophe Milesi; Anne Sirvent; Laura Kollen; Léa Domitien; Marjolaine Willems; Jean Donadieu; Christine Bellané-Chantelot; Federica Defendi; et al. (Scientific Reports)
Abstract Over 500 primary immunodeficiency diseases (PID) have been described, but immunological assessment after a severe infection is not routine. We aimed to evaluate the feasibility of a PID screening protocol and calculate PID prevalence in children admitted for severe infection in a pediatric intensive care unit (PICU). This monocentric retrospective study evaluated the feasibility of a PID monitoring protocol after severe infection in children aged 1 month to 16 years-old hospitalized in the Montpellier University Hospital from January 2018 to December 2020. Follow-up consultations at 3 and 12 months included the three main PID screening scores, comprehensive immunological and genetic screenings. Among 1125 children admitted to the PICU, 46 had severe infections and caused by bacterial (48%), viral (39%) or fungal (2%) pathogens. Before infection, none had completed any screening score recommended by dedicated societies (Jeffrey Modell Foundation, German Patients’ Organization for Primary Immunodeficiencies, French Reference Center for Hereditary Immunodeficiencies). At 3 months, three patients had a PID diagnosis (6.5% prevalence, 95% CI 1.4–17.9). These were associated with a deletion of chromosomal region 22q11.21 (DiGeorge syndrome), ELANE mutation (Elastase deficiency or Severe Congenital Neutropenia 1), and C5 deficiency Forty children (87%) presented immunological anomalies without a formal PID diagnosis. These persisted in only 4/17 children tested at 12 months. The most frequent abnormalities were low NK lymphocytes (41.18%), and abnormal B lymphocyte population distribution (25%). The observed PID prevalence post-severe infection matches previous reports, even with a high rate of viral infections, often overlooked. Systematic PID investigation after severe infection, regardless of the pathogen, should be implemented to improve early detection and treatment.